Case Studies of Men's Perceptions of Their Online Sexual Interactions With Young People: An Interpretative Phenomenological Analysis. (December 2019) - Kloess, Juliane A.; Larkin, Michael; Beech, Anthony R.; Hamilton-Giachritsis, Catherine E.
The aim of the present study was to gain an understanding of the perspectives of men who were convicted of committing a sexual offense that included online sexual grooming. It explores their experiences of illegal interactions with young people via Internet communication platforms, which progressed to physical meetings. Semistructured interviews were conducted with two men and analyzed using interpretative phenomenological analysis (IPA), providing in-depth accounts of their personal experiences. These are presented in a case study format. Three dominant themes emerged from the analysis: (a) fulfilling an unmet need, (b) spiraling cycle of use, and (c) confrontation with reality. Narrative tones employed by the two men were "being trapped in a lie, " analogous to a problem narrative through which their Internet use was presented as a poor and/or failed coping strategy to deal with life stress. Through a process of habituation, their Internet use spiraled out of control. A progression was described in terms of time spent on the computer, frequency and intensity of online interactions, and the impact this had on the men's personal lives, highlighting the "compulsive" nature of such interactions for them. A consideration of individual and situational vulnerability factors provides new insight into the progression of online sexual behavior and contributes to our understanding thereof.